COMPANY ADVISOR'S VIEW: ATTITUDES AND ABILITIES OF STUDENTS DURING AN INTERNSHIP - Irma Manda Negara; Nurul Hidayati (PEDAGOGIK : JURNAL PENDIDIKAN, 2020)
The world of work requires prospective workers to have skills according to the needs of the 21st century. Thus, it is important to provide work-based learning to provide work experience and develop student skills. The purpose of this study was to identify students' attitudes and skills during the internship from the point of view of company advisors as mentors and users. The method used is a qualitative method with company advisors as to the data source. Data collection was carried out by structured interviews, where interview questions were built based on the reference indicators used, namely work-based learning and learning innovation skills. The results showed that in general during the apprenticeship students have motivation, discipline, the adaptation of work ethics, responsibility in completing tasks and build good interactions with the institutional environment. From the aspect of student learning skills and innovation, there are still a number of things that need to be improved and trained such as problem-solving, communication, innovation, and creativity. Therefore, some of the skills included in learning innovation skills need to be applied in learning in order to prepare students before entering the workforce.